Efektivitas Sistem Penghantaran Liposom pada Katekin Sebagai Antioksidan - Verawaty Verawaty; Auzal Halim; Febriyenti Febriyenti (Jurnal Sains Farmasi & Klinis, 2016)
A study on the effectiveness of liposome delivery system of catechin as an antioxidant has been done. Liposome was derived from phosphatidylcholine of egg and cholesterol. The method used to prepared liposome in this research was thin layer hydration method by using rotary evaporator. Liposome was made in 3 formulas with different comparison between phosphatidylcholine and cholesterol. The first formula with ratio of 1:1; second formula with ratio of 1:2 and third formula with a ratio of 2:1. The result found that the observation with SEM seen sperical liposome and some oval liposomes. The level of entrapment efficiency (%EP) obtained on Formula I, II, and III were 24.49%, 24.67%, and 20.06%, respectively. We can conclude that the increase of cholesterol will increase the efficiency of drug entrapment. Test of the effectiveness of antioxidant found formula II was better than formula I and formula III. It can be concluded that the increase of cholesterol was able to improve the formulation and stability of liposome.